A study of lean six sigma implementation on improving automotive operational performance - Koay, Boon Hui (2016)
As global competition continues to grow, the pressure to improve to be the best becomes more and more intense. Thus, a combination of both Lean and Six Sigma which is called Lean Six Sigma (LSS) is born. This LSS method provides an over-arching improvement philosophy that incorporates powerful data-driven tools to solve problems and create rapid transformational improvement at lower cost. However, there are very few researches on LSS in Malaysian automotive industry. There still exists the gap in the body of knowledge in LSS in Malaysian automotive industry context which needs to be filled. Therefore, this research is aimed to investigate the practices of LSS implemented in a Malaysian automotive company, Vacuumschmelze (Malaysia) Sdn Bhd to identify the challenges of implementing LSS in Malaysian automotive company and to examine the impacts of LSS implementation on improving automotive company’s operational performance. First, a conceptual framework was developed based on a review of the literature, where “Define, Measure, Analysis, Improve, and Control’’ (DMAIC) are set as independent variables while operational performance (OP) variables including Cost and Waste Reduction (OPC), Quality (OPQ), Flexibility (OPF), Delivery (OPD), and Productivity (OPP) are dependent variable. While forming research design, interview with five interviewees from top management are carried out and 64 questionnaires are collected from employees in related department. Then, both of content analysis and statistical technique are used to analyse those data. Generally, all research objectives have been achieved. Through data collected from interview, different key processes and tools of LSS are found out in “Define, Measure, Analyse, Improve and Control” (DMAIC) stages. Challenges that are faced during implementation of LSS in the case study company include budget and time constraints, resistance from employees, fractured organizational culture, shortage of black belt, green belt and yellow candidates and picking the “right” projects. Beside this, findings also shown that LSS implementation brings positive impacts toward operational performance. Finally, managerial implication and recommendation for future study are proposed.